(untitled) (Research, Society and Development, 2022)
Human life is a right extremely protected by the Brazilian legal system, mainly by its Federal Constitution. However, when talking about dignified death, it is questioned to what extent this right is limited, in view of the principle of human dignity and autonomy of will. Thus, given the technological advances in the field of medicine, the evolution of society and the need for new discussions on the subject in the legal field, this paper seeks to debate and observe the limits of the right to life and the dignity of the human person in the face of modalities of Euthanasia and Orthothanasia, exploring the concepts of these modalities of abbreviating death, their origins, the world view of each of them, as well as understanding their legal position in the face of the Brazilian law. The methodology used was the review of bibliographies such as doctrines, laws and recent articles, for a better theoretical and legal basis for the work.